Digital electronic based portable device for colorimetric quantification of ketones and glucose level in human urine. (15th June 2023) - Mitra, Shirsendu; Basak, Mitali; Biswas, Saikat; Gooh Pattader, Partho Sarathi
Highlights: A digital photometer was developed for the quantification of glucose and ketone in human urine. A practical range for glucose (10 mg/dL−1400 mg/dL) and ketone (5 mg/dL–160 mg/dL) can be detected. A comparison study with samples from healthy as well as ill patients showed promising results. Unlike the conventional qualitative measurement, quantitative detection was demonstrated. Abstract: Development of a digital, frugal, portable testing device for quantification of glucose and ketones in the human urine sample is presented in this article. Based on the spectroscopic absorption principle, the colorimetric detection of the analytes is explored. Glucose in the human urine sample is quantified by the formation of the red-colored cuprous oxide due to the reaction with Benedict's solution. The reaction of urine with alkaline sodium nitroprusside is exploited to estimate the presence of ketones. A 3D printed portable photometer is fabricated, which can measure the glucose concentration ranging from 10 mg/dL to 1400 mg/dL and the ketone concentration spanning over 5 mg/dL to 160 mg/dL. This is helpful for preliminary detection of Diabetes related health issues such as Glycosuria or Ketonuria. Clinical sample analyses showed a reasonable match with the pathology test. The device is made digitally smart by integrating a Mobile App to store patient data.